The rights of access to information, participation and justice in environmental matters: feminist views on the Escazú Agreement: SOBRE AS OPINIÕES FEMINISTAS SOBRE O CONTEÚDO E O ESCOPO DO ACORDO DE ESCAZÚ - Cardona Zuleta, Elvigia; Vásquez Santamaría, Jorge Eduardo (Revista de Derecho Ambiental, 2024)
The article goes through a reflection on the rights in environmental matters in Colombia from a feminist perspective, which allows a critical reading of the advances that since the Political Constitution of 1991 and the jurisprudential developments that have currently taken place since the question: What are the contributions of feminisms to establish the criteria for the exercise of the rights to access to information, participation and justice in environmental matters in Colombia regarding the Escazú Agreement? It is based on a qualitative design of documentary review inscribed in the feminist paradigm in which the contents of the Escazú Agreement, constitutional provisions, constitutional judicial precedents, and feminist postulates are triangulated. Faced with the ratification of the Escazú Agreement, it is concluded that it may become an opportunity (or not) to complement or transform the patriarchal structures that still impose barriers to the exercise of women's rights. The feminist perspective allows us to establish the persistence of gender biases that must be addressed by the Colombian State with concrete actions so that girls and women have full access to these rights and achieve gender justice and equity.